The tetraspanin CD9 controls migration and proliferation of parietal epithelial cells and glomerular disease progression - Hélène Lazareth (Nature Portfolio, 2019)
In both focal segmental glomerulosclerosis (FSGS) and crescentic glomerulonephritis (CGN), kidney injury is characterised by the invasion of glomerular tufts by parietal epithelial cells (PECs). Here Lazareth et al. identify the tetraspanin CD9 as a key regulator of PEC migration, and find its upregulation in FSGS and CGN contributes to kidney injury in both diseases.